India's Navigation in the Geopolitical of IMEC and Regional Connectivity - Suryadipura, Dadan; Ghopa, Sabda Yancipta Wangsa (Universitas Sultan Ageng Tirtayasa, 2024)
As the trend of fossil fuel use declines, green hydrogen importing and exporting countries have created a new polarity for the development of the green hydrogen industry, one of which is through the India-Middle East-Europe Economic Corridor (IMEC) framework. The project, which aims to build regional connectivity for hydrogen infrastructure from Asia to Europe, has made India play a vital role in responding to various different interests ranging from the G7, the Quad, the Gulf States and the Middle East. Through qualitative research that is described explanatory, this study aims to explain India's role in navigating the dynamics of hydrogen geopolitics to reach the IMEC agreement. The results show that there is a three-way relationship dynamic between energy, international relations, and domestic politics of India with the G7, the Quad, and the Middle East countries which is manifested in the neo-mercantilism frame. This frame is seen as dominant in India's maneuvers that focus on the G2G approach to increase investment, research and technology, and regional stability, especially in the values of territorial integration and political independence.